2001
DOI: 10.1590/s0066-782x2001000100003
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic assessment of the different left ventricular geometric patterns in hypertensive patients

Abstract: The occurrence of ventricular hypertrophy undoubtedly represents an important marker of increased risk for cardiovascular events; therefore, the importance of identifying the patterns of hypertrophy in patients with hypertension is widely justified 1,2 . A recent study by Mensah et al 3 reported that measurement of the left ventricular mass on echocardiography proved to be better for predicting the evolutional process of hypertension as compared with other variables, such as systolic blood pressure, diastolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
(32 reference statements)
0
6
0
5
Order By: Relevance
“…In this study twenty eight percent (28%) of the hypertensive subjects had normal geometry while 72% had various altered geometric while 86% of the controls had normal geometry. Previous studies [ 20 - 23 ] carried out in Brazil, United States and Europe showed different frequencies for various LV geometric patterns. Ethnic differences and environmental factors might play an important role in the different geometric patterns.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In this study twenty eight percent (28%) of the hypertensive subjects had normal geometry while 72% had various altered geometric while 86% of the controls had normal geometry. Previous studies [ 20 - 23 ] carried out in Brazil, United States and Europe showed different frequencies for various LV geometric patterns. Ethnic differences and environmental factors might play an important role in the different geometric patterns.…”
Section: Discussionmentioning
confidence: 90%
“…Adaptation of the left ventricle to systemic hypertension is complex and it is characterized by functional and structural changes in the left ventricle. The old concept that the heart responds to systemic hypertension by developing concentric or eccentric hypertrophy have been challenged by recent studies[ 4 , 6 , 20 ]. Hypertension is now known to be associated with a wider spectrum of LV geometric patterns [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…В представленном нами исследовании у больных АГ в сочетании с БА наблюдаются бόльшие значения ИММЛЖ по сравнению с таковыми у лиц с АГ без сопутствующей патологии бронхиального дерева. Из доступной нам литературы известно, что имеются немногочисленные источники, указывающие на наличие у больных АГ в сочетании с БА бόльших значений массы миокарда ЛЖ по сравнению с таковыми у лиц с АГ без сопутствующей патологии бронхиального дерева [5,6,11,12]. Ведущей причиной развития гипертрофии ЛЖ у части больных АГ служит стабильность хронически повышенной нагрузки на миокард ЛЖ [9].…”
Section: Discussionunclassified
“…В исследовании Барсукова А. В. (2005) и его иностранных коллег при оценке структуры ЛЖ у пациентов с сочетанной патологией выявлена концентрическая гипертрофия ЛЖ, однако у пациентов с АГ в сочетании с БОЗ показана бóльшая степень концентричности по сравнению с изолированной АГ, что также подтверждается данными наших наблюдений [6,11].…”
Section: Discussionunclassified
“…Studies have found that ABPM values are more accurate and strongly correlated with LVH when compared to clinic blood pressure . Evidence suggests that blood pressure parameters measured from 24‐hour ABPM may serve as predictors of specific cardiac geometries . One pediatric study demonstrated differences in ABPM parameters by cardiac geometry; however, limited epidemiological evidence is available regarding the determinants of LV geometry in the pediatric population.…”
Section: Introductionmentioning
confidence: 99%